Neural correlates of deficits in affect regulation in methamphetamine abusers with and without a history of psychosis - Uhlmann, Anne (University of Cape Town, 2015)
Methamphetamine dependence has been associated with neurological damage resulting in potentially long-lasting changes in cognitive-affective processes, a range of behavioral problems and psychiatric disorders, including psychosis. Poor emotional control and maladaptive social behaviors have been linked to abnormalities in brain function and structure. However, the links between alterations in neurocircuitries, affect dysregulation, and psychotic symptoms in methamphetamine dependence are yet to be fully elucidated. This project aimed to delineate emotion regulation capabilities as well as brain structure and function in methamphetamine-dependent individuals, patients with a history of methamphetamine-associated psychosis, and healthy adults. The four cross-sectional studies presented here investigated socio-emotional behaviour using self-report questionnaires and social cognition tasks; and assessed neural activation during incidental emotion regulation, measured in an affect labelling task as part of functional magnetic resonance imaging. Additionally, structural magnetic resonance imaging and diffusion tensor imaging were employed to determine grey matter and white matter structural abnormalities, respectively, and to correlate findings with the presence/absence of affect dysregulation and psychotic symptoms. Both methamphetamine-dependent groups showed deficits in emotion regulation abilities, as evidenced by increased levels of aggression, impulsivity, and emotion reactivity. Further, social cognition capacities, including recognising emotions and inferring mental states of others, were diminished in both groups, with greater functional decrements in patients with methamphetamine-associated psychosis. These patients further demonstrated grey matter loss in frontotemporal brain regions and hippocampi, as well as globally reduced white matter integrity, compared to methamphetamine-dependent individuals; and structural deficits in prefrontal and temporal brain regions were associated with impaired affect regulation. Frontolimbic hypoactivation during emotion perception further suggests a role of diminished emotional salience attribution in the pathogenesis of methamphetamine-associated psychosis. Whereas methamphetamine-dependent individuals displayed prefrontal hyperactivation during affect labelling, potentially reflecting a compensatory activation to sufficiently regulate affect, or suggesting a cognitive bias towards the negative facial emotions. Longitudinal data and prospective research designs are needed to address the issue of causality as well as the issue of changes in brain structure and function over time as addiction and related psychopathology progress. Therapies targeting socio-emotional perception and affect regulation skills ultimately may help improve social functioning and mitigate relapse rates.